Development of low-cost Global Navigation Satellite System (GNSS) permanent base station for education - Sahdan, Ahmad Yusof; Zolkifli, Azrina; Othman Latpi, Norlydah; Hasim, Mohd Hazlan (2025)
This project introduces a low-cost, permanent Global Navigation Satellite System (GNSS) Real-Time Kinematic (RTK) base station system designed specifically for educational institutions. Leveraging commercially available GNSS hardware and open-source software tools, the system enables real-time centimeter-level positioning accuracy within a 15 km range. Several key technical components of this project are the development of a dedicated application layer that handles real-time data acquisition, correction transmission via Networked Transport of Radio Technical Commission for Maritime Services (RTCM) via Internet Protocol (NTRIP), and user interface interaction for both base and rover stations. The application integrates with GNSS modules through serial communication, processes RTCM data streams, and visualizes positioning outputs via a custom dashboard, enhancing usability for teaching and learning. Developed using lightweight frameworks compatible with embedded systems, the application ensures low resource consumption and high reliability. Field experiments at three locations showed the system's effectiveness in comparison to field observations using commercial GNSS equipment. The results of the field study show that the differences observed using this innovation meet the standards set by the Department of Surveying and Mapping Malaysia (JUPEM). The cost-effective nature of the system provides educational institutions the opportunity to deploy high-precision positioning infrastructure without the burden of commercial licensing, offering students hands-on experience with real-world geospatial technologies and strengthening institutional capabilities in technical education.